Aligning Order Picking Methods, Incentive Systems, and Regulatory Focus to Increase Performance. Issue 8 (25th February 2016) - de Vries, Jelle; de Koster, René; Stam, Daan
Abstract : A controlled field experiment investigates order picking performance in terms of productivity. We examined three manual picker‐to‐parts order picking methods (parallel, zone, and dynamic zone picking) under two different incentive systems (competition‐based vs. cooperation‐based) for pickers with different regulatory foci (prevention‐focus vs. promotion‐focus). The study was carried out in a warehouse erected especially for the purposes of order picking research. Our results show that when using a parallel picking method, a competition‐based incentive system increases productivity compared to a cooperation‐based incentive system, and that when using a zone picking method it is more productive to use a cooperation‐based incentive system. This pattern of results was especially pronounced for pickers with a dominant promotion focus. Dominantly, prevention‐focused pickers were more productive in zone picking with a cooperation‐based incentive system than a competition‐based incentive system, but in the other two picking methods the incentive systems delivered a similar productivity performance. No effects on order picking quality were identified. The analyses demonstrate that by aligning order picking methods, incentive systems, and regulatory focus, warehouses can substantially improve productivity.